Impact of Lifestyle on Knee Osteoarthritis in Mosul Hospitals - Rusul Sheet Ahmad, Bashar Jassim Al-Jwary, (Pakistan Journal of Medical & Health Sciences, 2023)
Background & Objectives: Osteoarthritis (OA) is the most prevalent form of arthritis. It is a chronic, degenerative disease of the musculoskeletal system that causes significant disability in patients all over the world. The knee is the most commonly affected joint by OA, especially in older people. Knee OA is a painful disorder that progresses with time and affects the whole knee joint, leading to varying degrees of severe joint failure. It can cause pain, stiffness, and swelling in the knee. It can also lead to disability ,and Lifestyle factors were found to be related to knee OA. This study’s aim was to evaluate how lifestyle choices affected knee OA in patients visiting hospitals in Mosul, Iraq. The specific objectives of the study were to 1 Evaluate demographic characteristics of individuals with knee OA. 2 Discover the lifestyle factors for patients with knee OA. 3 Determine the relationship between lifestyle and the severity of knee OA. Methods: A cross-sectional study design was adopted for the period extended from the 1st of December 2022, to the 20th of July 2023. It included 500 knee osteoarthritis patients collected from consulting clinics in four teaching hospitals in Mosul, Iraq, by using a developed interviewing questionnaire that assessed sociodemographic characteristics, health history, lifestyle factors, and the severity of knee OA. Results: The mean age of patients (59.4) The majority of the participants were female (83.4%). (74.6%) of the sample were housewives, (75.4%) lived in urban. The most common risk factors for knee OA were obesity (27.2%), and family history (47.4%). (90.8%)of the patients had low education level. Patients had bilateral joint OA(right and left) were 64.6%. Most of patients have a sedentary lifestyle. There are significant association between lifestyle domains like health self-responsibility, nutrition, physical activity, stress management, and spiritual growth with joint OA severity. The highest association between lifestyle domains and severity is seen in the areas of health self-responsibility, diet, and physical exercise. Conclusion: Certain demographic and socio-demographic factors, such as age, gender, education, residency, occupation, BMI, previous knee injuries, and family history, had a significant association with knee osteoarthritis patients. This study has shown that lifestyle factors play a role in the development and severity of knee OA. Physical inactivity, poor diet, and obesity are all major risk factors for knee OA. The findings can suggest that modification of lifestyle may be a protective against knee OA. Participants who reported being more physically active, eating a healthier diet, and maintaining a healthy weight were less likely to have severe knee OA. Interventions that target lifestyle factors may be beneficial in preventing and managing knee OA. Keyword: Knee Osteoarthritis, Life-Style, Factor